Application of Aquatic Insects (Ephemeroptera, Plecoptera And Trichoptera) In Water Quality Assessment of Malaysian Headwater - Suhaila Ab Hamid; Che Salmah Md Rawi (Tropical Life Sciences Research, 2017)
The Ephemeroptera, Plecoptera and Trichoptera (EPT) community structure and the specific sensitivity of certain EPT genera were found to be influenced by water parameters in the rivers of Gunung Jerai Forest Reserve (GJFR) in the north of peninsular Malaysia. The scores of EPT taxa richness of >10 in all rivers indicated all rivers’ habitats were non-impacted, having good water quality coinciding with Class I and Class II of Malaysian water quality index (WQI) classification of potable water. The abundance of EPT was very high in Teroi River (9,661 individuals) but diversity was lower (22 genera) than Tupah River which was highly diverse (28 genera) but lower in abundance (4,263 individuals). The lowest abundance and moderate diversity was recorded from Batu Hampar River (25 genera). Mayfly, Baetis spp. and Thalerosphyrus spp., stonefly Neoperla spp. and caddisfly Cheumatopsyche spp. were the most common genera found. Classification for all rivers using EPT taxa Richness Index and WQI gave different category of water quality, respectively. The WQI classified Tupah and Batu Hampar rivers into Class II and Teroi River (Class I) was two classes above the classification of the EPT taxa Richness Index. Struktur komuniti Ephemeroptera, Plecoptera dan Trichoptera (EPT) dan sensitiviti khusus genera EPT tertentu didapati dipengaruhi oleh parameter air di dalam sungai Hutan Simpan Gunung Jerai (HSGJ) di utara Semenanjung Malaysia. Skala kekayaan taksonomi EPT > 10 di semua sungai menunjukkan bahawa semua habitat sungai tidak terjejas, yang mempunyai kualiti air yang baik bersamaan dengan klasifikasi Kelas I dan Kelas II indeks kualiti air Malaysia (WQI) bagi air minuman. Kelimpahan EPT adalah sangat tinggi di Sungai Teroi (9,661 individu) tetapi kepelbagaian lebih rendah (22 genera) daripada Sungai Tupah yang sangat pelbagai (28 genera) tetapi lebih rendah (4,263 individu). Keanekaragaman yang paling rendah dan sederhana telah dicatatkan dari Sungai Batu Hampar (25 genera). Mayfly, Baetis spp. dan Thalerosphyrus spp., Stonefly Neoperla spp. dan caddisfly Cheumatopsyche spp. Adalah genera yang paling biasa dijumpai. Klasifikasi untuk semua sungai yang menggunakan Indeks Kekayaan taxa EPT dan WQI memberikan kategori kualiti air yang berlainan. WQI mengklasifikasikan sungai Tupah dan Batu Hampar ke Kelas II dan Teroi River (Kelas I) adalah dua kelas di atas klasifikasi Indeks Kesejahteraan EPT.